ESTIMATION OF THE SUSTAINABLE POTENTIAL OF FOURFINGER THREADFIN (Eleutheronema tetradactylum) IN THE WATERS OF TANJUNG JABUNG BARAT, JAMBI - Kurniawan, Ari; Yunita, Lauura Hermala; Vitaloka, Maya; Soliansyah, Rd. M. Irgi (Asian Journal of Aquatic Sciences, 2024)
One of the fisheries catches in Tanjung Jabung Barat is Fourfinger threadfin (Eleutheronema tetradactylum). Fourfinger threadfin is a commodity with a high economic value and has good taste, so many people catch it. Fourfinger threadfin is carried out continuously without considering the potential of the fish. If this continues to be done, it will cause a decrease in population. This research was conducted in August-October 2024. Secondary data on the results of the capture obtained from this study are data derived from the Tanjung Jabung Barat Fisheries Service from 2018 - 2022, including catches and efforts to catch Fourfinger threadfin. The data that was obtained was analyzed using Microsoft Excel. This research shows that the catch of Fourfinger threadfin in Tanjung Jabung Barat fluctuates every year. The highest CPUE value occurred in 2020, namely 3.688028, and the lowest was in 2021 at 1.28533. CMSY results and Optimum Effort of 727.4554 tons/year with Optimum Effort (Eopt) of 310,280 trips/year. With a Total Allowable Catch of 581.9643244. based on the data analysis that has been done, it can be concluded that the sustainable potential of Fourfinger threadfin in the waters of Tanjung Jabung Barat has not experienced overfishing. However, if there is an increase in fishing effort (trip), then the sustainable potential can be experienced in overfishing.